Real-Time Analytics in E-commerce: Strategies for Implementing Near Real-Time ETL Pipelines - Kushal Shah (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Near real-time ETL pipelines have emerged as a transformative force in e-commerce, enabling organizations to process and analyze data within seconds of its creation rather than relying on traditional batch methods. This article explores the architectural components, implementation strategies, and business applications of these advanced data processing systems. By examining pipeline architecture—including ingestion layers, change data capture mechanisms, stream processing engines, and storage solutions—alongside various implementation approaches like micro-batch processing and lambda architecture, the article demonstrates how these technologies deliver substantial business value. From inventory management and dynamic pricing to fraud detection and personalized customer experiences, real-time data pipelines provide competitive advantages through improved operational efficiency, enhanced decision-making capabilities, and more responsive customer interactions. Performance optimization techniques including effective partitioning, state management, and resource allocation further maximize the benefits of these systems while controlling costs.